Beyond roll-call voting: Sponsorship dynamics at the UN General Assembly - Seabra, P.; Mesquita, R. (International Studies Quarterly, 2022)
Research on the United Nations General Assembly (UNGA) has often privileged analyses on voting patterns, that is, how countries position themselves whenever a resolution is brought to a vote in each plenary session. However, voted resolutions comprise only a fraction of UNGA output, and much is still unknown about how countries behave before casting any votes. What takes place prior to and leading up to the adoption of resolutions? Even though the study of draft sponsorship remains underdeveloped, it can comprise a more valid empirical strategy to infer state preferences. This research note introduces the UN General Assembly Sponsorship Dataset, which encompasses the sponsorship behavior of every UNGA member from 2009 to 2019. We develop two novel empirical indices, priority and ownership, in order to ascertain draft relevance for each member state. We also use the new data to test longstanding arguments over vote-buying and North versus South coalitions in the UNGA. Our findings confirm mainstream conclusions for the former but challenge prevailing assumptions on the latter.